Public health and safe water in Latin America: Sustainable solutions to climate change (Research, Society and Development, 2025)
Growing population demand and anthropogenic pollution, which introduces microplastics, heavy metals, pesticides and bacterial pathogens into bodies of water, exacerbate the water crisis, reducing the availability and quality of drinking water. This scenario increases the incidence of gastrointestinal diseases, such as hepatitis, cholera and diarrhea, responsible for millions of deaths annually. In Latin America, and particularly in Ecuador, the problem is exacerbated by prolonged droughts and the lack of updated data on the relationship between public health and access to safe water, making it difficult to formulate effective policies. The objective of this article is to present a study on public health and safe water in Latin America. Helicobacter pylori, a gram-negative bacterium associated with severe gastric pathologies, affects up to 70% of the Ecuadorian population, reflecting the high vulnerability of the region. This study suggests that the low quality of drinking water significantly increases the prevalence of waterborne diseases. Therefore, it emphasizes the need to develop and implement sustainable purification technologies, along with comprehensive policies to ensure equitable and continuous access to safe drinking water.